2015
DOI: 10.1515/ijsl-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Identity negotiation in a super-diverse community: The fuzzy languaging logic of high school students in Soweto

Abstract: This article reports on multilingual adolescent youth's negotiation of identities in a languaging South African environment. Focus group dialogues of 17 Grade 11 multilingual students from the South Western Townships (Soweto) in Johannesburg were analysed using conversational analysis techniques from a selected data pool that was generated over a period of three hours. The results of the study show a rift between classroom language and out of school language practices. We demonstrate that (i) the Soweto youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This belief and practice of teachers regarding learners' bilingualism/multilingualism/plurilingualism as a deficit rather than as an empowering resource has been studied extensively elsewhere in schools (e.g. see Banda 2010Nkadimeng & Makalela 2015Makalela 2016; for the case of South Africa). Further interactions with teachers in our study revealed that teachers in private schools were under pressure from parents to have pupils learn to speak English as early as possible (cf.…”
Section: (A) Respondentmentioning
confidence: 99%
“…This belief and practice of teachers regarding learners' bilingualism/multilingualism/plurilingualism as a deficit rather than as an empowering resource has been studied extensively elsewhere in schools (e.g. see Banda 2010Nkadimeng & Makalela 2015Makalela 2016; for the case of South Africa). Further interactions with teachers in our study revealed that teachers in private schools were under pressure from parents to have pupils learn to speak English as early as possible (cf.…”
Section: (A) Respondentmentioning
confidence: 99%
“…The aforementioned concerns allude to the studies and reflections of García;Alves (2019), García;Wei (2014), García (2020), Blackledge;Creese (2011), Canagarajah (2013), Makalela (2015Makalela ( , 2016Makalela ( , 2017, Dhokotera (2021), Nkadimeng;Makalela (2015), among others, who have long been exercising agency in specific contexts with a view to promote more democratic education and, thus, social participation of the people in disadvantageous positions and conditions.…”
Section: To Start the Conversationmentioning
confidence: 99%
“…Many studies explore the roles of language in national development and unity (for example, Emeka-Nwobia 2015;Danladi 2013;Obiegbu 2015) and those that investigated patterns of self-assertiveness among ethnic groups characterised by ethnolinguistic vitality (e.g. Nkadimeng and Makalela 2015;Garri and Mugaddam 2015;and Chew 2014). Kamran andMansoor (2017), andDressler andDressler (2016) investigate language use with ethnolinguistic colourations on Facebook.…”
Section: Introductionmentioning
confidence: 99%